TEACHING ACCENTS: PROBLEMS AND SOLUTIONS - Syarifuddin Syarifuddin (Universitas Yudharta Pasuruan, 2017)
Standard English has many different accents. Teachers of English in Indonesia might have problems in their classrooms such as intelligibility, negative attitudes towards accents, differences of accents in different materials and between students’ needs/expectation and teacher’s awareness of variations. This article has addressed some solutions. Some of them are: Teachers should teach the varieties of Standard English they master either American English or British English as a model in order to provide mutual intelligibility; teachers should try changing students’ attitudes toward by giving them an explanation about variations; teachers should give students explanation first about differences in dictionaries; teachers should master variations, at least AE and BE. By this recognition of the problems and understanding the solutions, the writer believes that teachers can address/solve the problems.